COMPARATIVE ANALYSIS OF TECHNOLOGICAL PROCESSES OF KURITSKY EQUIPMENT 2SV-10 AND TOWER DRYING EQUIPMENT (Academia Science Repository, 2023)
In this article, technical and technological indicators, advantages and disadvantages of SBO and 2 SBO10 drying equipment in the technological process of cotton drying at the Rishton cotton ginning plant were considered. Also, information about the tests of Namangan 77 and Andijan selection varieties of cotton raw material for the analysis was disclosed.